2021
DOI: 10.1186/s13104-021-05467-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of calcium-dependent protein kinase 4 (CDPK4) as Toxoplasma gondii vaccine target

Abstract: Objectives Toxoplasma gondii (T. gondii), an obligate intracellular apicomplexan parasite, could affect numerous warm-blooded animals, such as humans. Calcium-dependent protein kinases (CDPKs) are essential Ca2+ signaling mediators and participate in parasite host cell egress, outer membrane motility, invasion, and cell division. Results Several bioinformatics online servers were employed to analyze and predict the important properties of CDPK4 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It has been indicated that the use of CDPK1, CDPK2 and CDPK3 in the form of attenuated, recombinant and DNA vaccine induced high levels of Th1-associated cytokines, and prolonged survival and decrease brain cysts in vaccinated mice [13][14][15][16][17]. In addition, in silico tools have predicted recently potential immunogenic B-and T-cell epitopes for CDPK4 and CDPK7, pointing out their potential as appropriate vaccine candidates against T. gondii [18,19].…”
Section: Introduction: Vaccine and Diagnostic Strategies In Toxoplasm...mentioning
confidence: 99%
“…It has been indicated that the use of CDPK1, CDPK2 and CDPK3 in the form of attenuated, recombinant and DNA vaccine induced high levels of Th1-associated cytokines, and prolonged survival and decrease brain cysts in vaccinated mice [13][14][15][16][17]. In addition, in silico tools have predicted recently potential immunogenic B-and T-cell epitopes for CDPK4 and CDPK7, pointing out their potential as appropriate vaccine candidates against T. gondii [18,19].…”
Section: Introduction: Vaccine and Diagnostic Strategies In Toxoplasm...mentioning
confidence: 99%
“…Hence, the discovery and design of an effective vaccine to control and prevent toxoplasmosis is very important, especially in humans and domestic animals. In this regard, various in silico-based studies suggest various antigens as suitable candidates for vaccine design [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Calcium-dependent protein kinases (CDPKs) are a class of serine/threonine kinases that express in apicomplexans, ciliates, and plants [33].…”
Section: Introductionmentioning
confidence: 99%